Tax Management Dipengaruhi Fasilitas Pajak, Leverage, Transfer Pricing, Fixed Assets Intensity, dan Political Power - Ema Aulia Erwanti; Trisni Suryarini (Politeknik Ganesha Medan, 2022)
Tax management is still an ongoing issue. This is done because the company seeks to maximize profits by minimizing the tax burden paid, besides that tax management actions occur because there are differences in objectives between the government and the company. The government aims to optimize state revenue through tax revenue, while companies view taxes as a burden for reducing profits. This study aims to understand and examine the effect of tax facilities, leverage, transfer pricing, fixed assets intensity, and political power on tax management. The population in this study uses the property and real estate industry sector companies in 2017-2020 as many as 80 companies. The research sample was taken using purposive sampling technique with the acquisition of a sample of 16 companies dan 64 research data with outlier data as many as 24 units of analysis. The data processing technique method in this study uses descriptive statistical data analysis, classical assumption test, multiple linear regression analysis, hypothesis testing using partial significant test (t-test) with IBM SPSS software version 25. The result prove that tax facilities and political power have a significant negative effect on tax management. In addition, leverage and transfer pricing have a significant positive effect on tax management and fixed assets intensity does not have a significant negative effect on tax management.